Predisposed to volunteer?: Personality traits and different forms of volunteering - Ackermann, Kathrin (Sage, 2020)
In this article, we evaluate the psychological basis of different forms of volunteering. To date, our knowledge about the relationship between personality and volunteering as an important facet of the social fabric is limited. Applying the Five-Factor Model of Personality (Big Five), we scrutinize this relationship in a comprehensive manner. We consider formal and informal volunteering as well as online volunteering as a new form of social participation. Empirically, we analyze a representative population sample of Switzerland using logistic regression models. We find that extraversion is the most consistent driver of volunteering. The effects of the remaining traits differ across the forms of volunteering. additional analyses indicate that situational factors may moderate these relationships.
In: Nonprofit and voluntary sector quarterly, 48 (2019), Nr. 6. pp. 1119-1142. ISSN 0899-7640 (Druck-Ausg.); 1552-7395 (Online-Ausg.)